The Influence of Leadership Style, Communication, and Competence on the Work Spirit of Employees in the Fisheries and Food Service of Pasaman Regency - Endarwita Endarwita; Ria Widhia Sari; Yurasti Yurasti (Transpublika Publisher, 2025)
This study examines the influence of leadership style, communication, and competence on employee work spirit at the Pasaman Regency Fisheries and Food Service. The study population included 33 individuals from the mentioned department. The sampling method used in this research was total sampling. Data was gathered through interviews and questionnaires, and analyzed using multiple linear regression. The findings revealed that leadership style significantly affects employee work spirit (p=0.013<0.05), while communication showed no significant impact (p=0.177>0.05). Employee competence demonstrated a significant effect (p=0.040<0.05), and collectively, all three variables showed a significant influence on work spirit (p=0.003<0.05). The coefficient of determination (R²=0.611) indicated that these variables account for 61.1% of the variance in employee work spirit. These findings underscore the importance of effective leadership and competence development in enhancing employee work spirit within public service organizations.